Pengembangan Sistem Aplikasi Penjualan Keripik Pisang Berbasis Web - Nafian, Zidni Ilman; Ikrimach, Ikrimach (LPPM Universitas Mulia, 2024)
This research aims to develop a web-based application to support the sale of banana chips at Toko Keripik Njik-Njik. Currently, the store relies on Instagram social media as the main means of sales and marketing, which limits the reach of consumers to users of the platform. The application developed is expected to expand the market while simplifying the sales process and data management digitally. The main features designed include product catalogs, detailed product information, customer reviews, online ordering systems, and admin dashboards to monitor and manage stock and sales data in real time. The development process applies the Agile method with an incremental approach, starting from needs analysis, system design, implementation, testing, to the final implementation and evaluation stage. This approach allows each stage of development to produce features that can be directly tested and adjusted to user needs. This research contributes as a digital solution to improve store operational efficiency, expand marketing reach, and be an example for other UMKM in utilizing technology to drive their business growth.